SAK-ETAP's Impact on Financial Reports in Batik SMEs, Sidoarjo Regency: Dampak Implementasi Akuntansi Berbasis SAK-ETAP pada Laporan Keuangan UKM Batik Tulis di Kabupaten Sidoarjo. - Fibriani Awalia Ramadhani; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2022)
The problem that is often faced by SMEs is the lack of knowledge in making financial reports due to a lack of knowledge about accounting science. In addition, SMEs have limited time in making financial reports. Therefore, SMEs need to know the financial statements based on SAK ETAP. So that they can record business transactions with financial statements. Starting from journals, ledgers, income statements and balance sheets. The purpose of this study was to find out how the implementation of accounting based on SAK-ETAP on the quality of financial reports in small and medium-sized Batik Tulis in Sidoarjo. The object of this research is UKM Batik Tulis Jetis Sidoarjo. Researchers conducted observations and interviews with batik SME actors to identify the financial statements of SMEs. Test the validity of the data using a triangulation test. Technical analysis of the data uses four stages, namely data collection, data extraction, data display, and conclusion drawing. Based on interviews with SMEs making batik in Sidoarjo, no one has yet implemented SAK ETAP for their business financial records. On average they only record transactions that occur, without making financial statements. Highlights: Lack of accounting knowledge: SMEs face challenges in making financial reports due to a lack of understanding of accounting principles. Limited time: SMEs often struggle to allocate sufficient time for creating financial reports amidst their other business responsibilities. Implementation gap: The research highlights that the SMEs in the batik industry in Sidoarjo have not yet adopted SAK ETAP for their financial records, focusing only on recording transactions without producing comprehensive financial statements. Keywords: SMEs, financial reports, SAK ETAP, batik industry